2006
DOI: 10.1783/147118906776276440
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of cervical ectopy to chlamydia infection in young women

Abstract: Objective Genital Chlamydia trachomatis infection is the most common bacterial sexually transmitted infection (STI) in the UK. Behaviours including multiple sex partners and inconsistent condom use, and biological factors such as cervical ectopy, may increase susceptibility to STIs. Cervical ectopy is thought to increase risk of chlamydia infection by exposing columnar epithelium to a potential infectious inoculum. This study aimed to determine whether chlamydia was more prevalent in young women with cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 12 publications
1
52
0
1
Order By: Relevance
“…Although most women are asymptomatic, the condition can present with irregular discharge and postcoital and intermenstrual bleeding. 6,7 It has been suggested that cervical ectopy may be a potential risk factor for various sexually transmitted diseases, including Chlamydia trachomatis, 8 HIV, 9 and HPV infection. [10][11][12] In a previous work we showed that the detection of HPV DNA was more common in cervical ectopy than in cytology normal controls.…”
Section: Introductionmentioning
confidence: 99%
“…Although most women are asymptomatic, the condition can present with irregular discharge and postcoital and intermenstrual bleeding. 6,7 It has been suggested that cervical ectopy may be a potential risk factor for various sexually transmitted diseases, including Chlamydia trachomatis, 8 HIV, 9 and HPV infection. [10][11][12] In a previous work we showed that the detection of HPV DNA was more common in cervical ectopy than in cytology normal controls.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent girls and young women do not yet have fully mature reproductive and immune systems, so they may be unable to mount a strong defense against infection; 15 specifically, they are more likely to have cervical ectopy, which has been shown to be associated with CT across most studies. 7,[16][17][18][19] Ectopy is thought to increase the risk of infection by allowing exposure of more susceptible columnar epithelial cells. In addition to biologic considerations, there may also be social and contextual factors that broadly increase the vulnerability of this age group to CT infection.…”
Section: Discussionmentioning
confidence: 99%
“…Chlamydia rates are also higher among females than among males in the USA, England and Australia (11, [16][17]. Several studies have indicated that females may be more biologically susceptible to chlamydia than males (18,19). Furthermore, they are also more likely to seek health care (19,20).…”
Section: Discussionmentioning
confidence: 99%